Anticoagulants for the treatment of venous thromboembolism in patients with cancer: A comprehensive systematic review, pairwise and network meta-analysis. (August 2020) - Sidahmed, Shima; Abdalla, Ahmed; Kheiri, Babikir; Bala, Areeg; Salih, Mohammed; Bachuwa, Ghassan; Kafri, Zyad; Kuderer, Nicole M.; Lyman, Gary H.
Highlights: NOACs had reduced VTE recurrence and bleeding compared with VKAs. NOACs had reduced VTE recurrence, but higher bleeding risks compared with LMWHs. LMWHs had reduced VTE recurrence and similar bleeding compared with VKAs. Abstract: Cancer-associated venous thromboembolism (VTE) is associated with high VTE recurrence and bleeding. We included all randomized clinical trials that evaluated the efficacy and safety of various anticoagulants in cancer-associated VTE. Trial-level data were extracted from 13 trials. Aggregate odds ratios (ORs) were calculated using direct and network meta-analysis. The primary outcome was VTE (pulmonary embolism and/or deep vein thrombosis) recurrence. Secondary outcomes were major bleeding and all-cause mortality. We identified 13 trials with 4869 patient-years of follow-up (6595 total patients; mean age 62.4 ± 12.2; 50.4 % female; 17.7 % hematological malignancies). The most common cancer type was colorectal and 48 % had metastatic cancer at baseline. Compared to vitamin-K-antagonists (VKAs), non-vitamin-K-antagonist-oral-anticoagulants (NOACs) were associated with significantly reduced VTE recurrence (OR, 0.58; 95 % CI, 0.40-0.83) and reduced major bleeding risks (OR, 0.56; 95 % CI, 0.35-0.91). However, no differences were observed in the subgroup analysis of patients with active cancer. Although NOACs were associated with reduced VTE recurrence compared with low-molecular-weight-heparin (LMWHs) (OR, 0.46; 95 % CI, 0.25- 0.85), there was a significant increased major bleeding in high-quality trials. LMWHs were associated with significantly reduced VTE recurrence compared with VKAs (OR, 0.52; 95 % CI, 0.39-0.71) and similar bleeding risks. Conclusions: Among patients with cancer-associated VTE, NOACs were associated with significantly reduced VTE recurrence and bleeding compared with VKAs, however, with similar outcomes in the active cancer population. NOACs were associated with reduced VTE recurrence but higher bleeding risks compared with LMWHs. LMWHs were associated with significantly reduced VTE recurrence and similar bleeding compared with VKAs.